Dang Gui Bu Xue Tang, a conventional Chinese herb decoction, ameliorates radiation-induced heart disease via Nrf2/HMGB1 pathway - Huang, Yifan; Cheng, Minghan; Wang, Xiaoye; Dong, Hongliang; Gao, Jian (Frontiers in Pharmacology, 2023)
Radiation-induced heart disease (RIHD), characterized by cardiac dysfunction and myocardial fibrosis, is one of the most common complications after cardiothoracic radiotherapy. Dang Gui Bu Xue Tang (DBT) is a conventional Chinese herb decoction composed of Radix Astragali membranaceus (RAM) and Radix Angelicae sinensis (RAS) at a ratio of 5:1, famous for its “blood-nourishing” effect. In this study, we aimed to investigate the cardioprotective effect of DBT on RIHD. C57BL mice at 8 weeks of age were divided into five groups, namely Control, Radiation, RDBT51 (Radiation with DBT, RAM:RAS=5:1), RDBT11 (Radiation with DBT, RAM:RAS=1:1), and RDBT15 (Radiation with DBT, RAM:RAS=1:5). We mainly found that radiation in the cardiothoracic region led to significant left ventricular systolic dysfunction, myocardial fibrotic lesions and cardiac injury accompanied by abnormally increased myocardial HMGB1 protein levels. Administration of conventional DBT significantly ameliorated left ventricular systolic dysfunction, alleviated myocardial fibrosis, and counteracted cardiac injury, all of which supported the protective effect of DBT on RIHD, involving upregulation of myocardial Nrf2 protein levels and downregulation of HMGB1 protein levels as underlying mechanisms. In conclusion, DBT exerts a significant protective effect on RIHD, and the Nrf2/HMGB1 pathway probably plays an important role in this protective effect.